Assessment of groundwater quality in the urban development industrial area of Jalna district. (5th February 2023) - Ismail, H.; Abed, Syed
Analyses on paper, including physicochemical testing of Jalna region water. The main focus is on water contamination due to iron as steel re-rolling mills are present in Jalna that discharge their waste. It has been found that in almost all industrial areas having steel rolling mills, water contamination is at its peak. Hence, the study was completed to know the iron and calcium contamination in the underground and surface water present there. This research uses statistical methods to examine water samples collected in 8 different tehsils in Jalna. In the paper, analysis of data was done from laboratory experimentation work performed on water samples collected from the study area. Various physical and chemical parameters were observed and analysed using regression analysis. The values obtained were compared with the Indian standards and permissible limits of the Bureau of Indian Standards (BIS). On analysis, it was observed that the parameters of different elements present in the sample water were within permissible limits of the standard. The paper has an introduction and description of different types of pollutants with regression analysis, discussing the results before the conclusion and suggestions.